DNA barcoding of aphid-associated ants (Hymenoptera, Formicidae) in a subtropical area of southern China - Junaid Ali Siddiqui; Zhilin Chen; Qiang Li; Jun Deng; Xiaolan Lin; Xiaolei Huang (ZooKeys, 2019)
As one of the most abundant and complex groups of terrestrial insects, ants have associations with many other organismal groups, such as hemipteran insects producing honeydew. With the aim of expanding the knowledge base of ant species associated with aphids, this study analyzed mitochondrial COI barcodes of 301 ant samples for 37 aphid-associated ant species in a subtropical area of southern China. Sequence analyses revealed that the intraspecific and interspecific distances ranged from zero to 7.7%% and 0.2 to 31.7%, respectively. Three barcoding approaches – Automatic Barcode Gap Discovery, Bayesian Poisson Tree Processes and Generalized Mixed Yule-coalescent – were used to help delimit ant species based on COI sequences, and their results corresponded well with most of the morphospecies. All three approaches indicate cryptic diversity may exist within Tetramorium bicarinatum and Technomyrmex albipes, with intraspecific genetic distances of 7.7% and 6.24%, respectively. Our analyses also reported five species for the first time from Fujian Province of China, and the COI sequences of nine species are newly added into the GenBank. This study provides information about species diversity of aphid-associated ants in subtropical China and compiles a DNA barcode reference library for future ant barcoding work.